REMOTE-CONTROLLED TWO-WHEELED SELF-BALANCING ROBOT - Filipek, Przemysław (Journal of Technology and Exploitation in Mechanical Engineering _ARCHIVE ISSUES, 2022)
The article presents the design and fabrication of a remotely controlled two-wheeled self-balancing robot, along with its mobile control by means of an application on a phone displaying basic parameters in a terminal. A 3D model made in SolidEdge software, the electronic components used to build the robot and electronic schematics and software are presented. Real-world tests were conducted that demonstrate the robot's operation. The robot can be used for educational and commercial purposes, as well as in the human home environment.